ASSA13-03-15 The Role of P66shc Adapter Protein in the Inhibitory Action of Curcumin on Cardiomyocyte Apoptosis Induced by AngII. (29th April 2013) - Ming, Zhang; Jin, Wei; Rui, Yan; Hu, Shan; Lin, Lin; Yanhe, Zhu
Abstract : Objective: To explore the role of p66shc adapter protein in the cardiomyocyte apoptosis induced by AngII, and the effects of curcumin pretreatment. Methods: Neonatal rat cardiomyocytes (NRCMs) were prepared from 1 to 2 days old Sprague-Dawley rats, and were randomly divided into five groups, including normal control group, 10 –11 M AngIIgroup, 10 –9 M AngIIgroup, 10 –7 M AngIIgroup, and 10 –7 M AngII+curcumin group. The cell viability was measured by MTT. The level of reactive oxygen species (ROS) in the whole cell and cell apoptosis rate were measured by the flow cytometry. Mitochondrial membrane potential (MMP) was detected using a fluorescence microplate reader, and the protein expression of phosphorylated and total p66shc was detected using western blot. Results: With the increasing AngIIconcentration on NRCMs, cell viabilities and MMP levels were gradually decreased, and the levels of ROS in the cardiomyocytes and the cell apoptosis rates were both increased (P < 0.05). Moreover, the pretreatment of curcumin could significantly attenuate the cardiomyocyte injury induced by AngII (P < 0.05). The protein expression of phosphorylated p66shc in the whole cell lysates and total p66shc in the mitochondria were both increased in a dose-dependent manner when NRCMs were exposed to 10–11 to 10–7M AngII for 24h (P < 0.05). When NRCMs were exposed to 10–7M AngII, the pretreatment of curcumin could significantly down-regulate the protein expression of phosphorylated p66shc in the whole cell lysates and total p66shc in the mitochondria (P < 0.05). Conclusions: p66shc plays an important role in the cardiomyocyte apoptosis induced by AngII, and curcumin could attenuate AngII induced cardiomyocyte injury through down-regulating the protein expression of p66shc.